2019
DOI: 10.1088/1742-6596/1276/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of drag and lift coefficient of a Sport Utility Vehicle (SUV)

Abstract: The paper describes the modeling and analysis of a Sport Utility Vehicle (SUV). The present study mainly focuses on the reduction of aerodynamics drag and lift coefficient of a car, which helps to improve the vehicle performance and fuel efficiency. Usually the aerodynamic drag and lift is insignificant at low vehicle speed but the magnitude of air resistance becomes considerable with accelerating the vehicle. The Computational Fluid Dynamics (CFD) helps to analyze the flow stream around a SUV. The modeling so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A significant increase of pressure contours in front of the model is due to the result of high-velocity acceleration, parallel with Bernoulli's principle when the high-pressure area corresponds with the low-speed area of the speed profile [69]. Research by Samy et al, [22] further indicates that the front model represents the high value of static pressure whilst pressure drop is experienced at the back and under the body of the vehicle which affects drag and lifts coefficients as exemplified in Figure 14 [22]. Major pressure reduction can be seen on the roof of the TATA Safari model due to the low-velocity acceleration as compared to the Ahmed model (the simple bodies).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…A significant increase of pressure contours in front of the model is due to the result of high-velocity acceleration, parallel with Bernoulli's principle when the high-pressure area corresponds with the low-speed area of the speed profile [69]. Research by Samy et al, [22] further indicates that the front model represents the high value of static pressure whilst pressure drop is experienced at the back and under the body of the vehicle which affects drag and lifts coefficients as exemplified in Figure 14 [22]. Major pressure reduction can be seen on the roof of the TATA Safari model due to the low-velocity acceleration as compared to the Ahmed model (the simple bodies).…”
Section: Discussionmentioning
confidence: 83%
“…This model can be divided into a few categories such as TATA Safari, TATA Nano, and TATA Indica. The findings of literature reviews revealed that Samy et al, [22] applied the TATA Safari model for the SUV segment with the length (L) of 4655 mm and the width (W) of 1855 mm [22]. The angle of the windshield is 32° and it is located 100 mm from the centre of the front wheel as shown in Figure 6.…”
Section: Basic Car Shapesmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous findings have explained that the difference in vehicle model geometry is important and varieties of vehicle designs have been used in experimental and numerical research [14]- [17]. Based on Samy et al, the study on the aerodynamic analysis without crosswind involving a Sport Utility Vehicle (SUV) focusing on the drag and lift coefficient [17].…”
Section: Introductionmentioning
confidence: 99%